Mengidentifikasi Pengaruh Bakat Dan Minat Belajar Peserta Didik Ditingkat SMA Terhadap Pembelajaran - Ririnni, Arman; Afrahamiryano, Afrahamiryano (Peneliti.net, 2024)
Education is essentially an internal process that aims to develop personality and abilities inside and outside oneself. Developing interests and talents is part of it. This research examines the influence of high school students' interests and talents on the learning process. This research uses literature study research methods and qualitative research methods. The sample used several related journals from the last 10 years and collected data sourced from interviews with students of SMA N 01 BUKIT SUNDI. The research results show that interests and talents are very influential in the learning carried out by high school students. The strategy implemented by class teachers is to integrate interest and talent material into learning material, choose appropriate methods and facilities, remediate learning, build communication, provide examples, appreciate and know, identify and choose supporting programs. Interest in learning has a very big influence on learning outcomes, because if the learning material studied does not match their interests, then students will not learn well because it is not interesting to them. Teacher qualifications need to be further improved so that students' interest in learning and talents are better than before.